Effect Glogster on Students’ Academic Achievement in Selected Basic Technology Concepts in Ilorin Metropolis - Eno Ndarake Asuquo; Samuel A Onasanya; Temitayo Omolara Onasanya; Gboyega Ayodeji Aladesusi (Universitas Pendidikan Indonesia (UPI), 2022)
This study examined the Effect of Glogster on students’ Academic Achievement in Selected Basic Technology Concepts in Ilorin Metropolis. The study adopted a quasi-experimental type, of pre-test, post-test, non-randomized, control group design. The design is a 2 x 2 factorial design. The sample for the study comprised of 24 males and 20 females (44) students selected from JSS II classes of selected two schools. School A was assigned as the experimental group, while School B was the control group. The purposive sampling technique was used to select intact classes used for the study. Four research questions were raised and answered, while two research hypotheses were formulated and tested. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that there was no significant difference in the mean scores’ performance of male and female students that were exposed to Glogster and there was no significant difference between male and female students’ attitudes towards the use of Glogster for learning. The study concluded that learning can be enhanced among secondary school’ students if appropriate technology like Glogster is deployed for learning. Therefore, it was recommended that secondary school students be encouraged to deploy Glogster for learning irrespective of their gender.